Protection of child offenders at the pre-trial process in Malaysia: Are we doing enough? - Ahmad, Nadzriah; Hamid, Abdul Ghafur@Khin Maung Sein; Wok, Saodah (e-International Publishing House Ltd (e-IPH), United Kingdom, 2020)
The adverse effects of the pre-trial process on child offenders are damaging, particularly on their mental, emotional and physical developments. This study adopted the qualitative design, and the results indicate that the majority of the child offenders affirmed that they were subjected to some forms of ill-treatment during the pre-trial process, particularly during the investigation stage, where they are subjected to questioning. Thus, the results can facilitate the policymakers in strengthening and developing the current laws and policies and to introduce diversion programmes as an alternative to the juvenile justice system in Malaysia.